Clinical approach to palatal necrosis in an immunocompromised patient: A dental professional’s role (Indian Journal of Case Reports, 2020)
Mucormycosis is a rare, emerging fungal infection caused by Mucormycetes/Zygomycetes/Phycomycetes. It is an airborne infection that shows systemic dissemination. The prevalence of mucormycosis varies and is 14/100,000 population in India. The rhino-orbitocerebral form is common in the maxillofacial region. Effective antifungal therapy, surgical debridement, a reversal of immunosuppression, and management of the underlying medical condition are the treatment modalities followed in mucormycosis. The dental professionals play a pivotal role in the early diagnosis of mucormycosis allowing timely initiation of the therapy and surgical debridement reducing morbidity and mortality. This case report presents a case of mucormycosis affecting the left maxillary posterior region in a 42-year-old male who reported with a chief complaint of swelling, nasal obstruction, nasal discharge, and headache, diagnosed at an early stage, and treated with surgical debridement through a multidisciplinary approach.